Value Rationality Dalam KHI Pasal Ihdad Bagi Suami - Mohamad Maqin; M. Abi Mahrus Ubaidillah (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2023)
Abstract: Ihdad is a period of mourning for wives whose husbands died without jewelry and perfume. This means that only the wife is obliged to fulfill Ihdad. However, in KHI Article 170 paragraph (2) a husband whose wife has died must mourn politely. By using Max Weber's Theory of Social Action, the author wants to reveal the purpose of the Drafting Team as actors of Social Action from this article. And what will be examined is (1) The purpose of the Drafting Team in adopting article 170 paragraph (2) KHI. (2) Max Weber's Social Action Theory perspective on Ihdad for husbands. The focus of the research study is normative law. And in the form of library research. Data were analyzed using descriptive analytical methods by outlining Max Weber's entire theory of social action, especially Max Weber's 4 ideal types. Meanwhile, the data analysis uses an analytical approach to statutory regulations. It can be concluded (1) The aim of the KHI Drafting Team as social action actors in producing the Ihdad article for husbands in KHI Article 170 paragraph (2) is to respect the practice of Ihdad for husbands which has long been carried out by the community in certain areas before KHI existed and is one of The ideals of formulating the KHI as a legal answer to problems that arise in Indonesian Islamic society can be realized, even though the article does not yet have a definite legal label, because this is a form of caution from the Drafting Team. (2) that the goal of the KHI Formulation Team is included in the type of social action classified by Weber, in the form of Value Rationality, where with this type of motive the Formulation Team has appreciated the action. practice Ihdad to their husbands and these are the values they want to live by and fight for.